Promoting culturally informed and sensitive practice in day-care centers—a contribution to the professionalization of day-care teachers - Buchner, Ursula Gisela; Eberl, Constanze Maria Luise; Hess, Markus (Frontiers in Psychology, 2023)
Background: Based on the growing number of families and young children with a refugee background in Germany, day-care teachers face enormous challenges regarding culturally informed practice. The project “Gemeinsam stark durch den Start” (Stronger together by starting together) addresses these challenges on various levels. At the level of day-care teachers, training in culturally informed and sensitive education is combined with reflection sessions about their own attitudes and prevailing intercultural norms, thus contributing to the professionalisation of day-care teachers. Aim: This paper focuses on mechanisms of action that contributed to the effectiveness of the training from two perspectives: the day-care teachers’ perspective and the trainers’ perspective. Methods: Staff members of 11 German day-care centres underwent graded online training sessions (team and in-depths trainings) addressing intercultural topics. All participants were presented with a questionnaire for their training evaluation before and after the training sessions. Also, participants of the in-depths trainings participated in semi-structured interviews on the training. Furthermore, qualitative interviews were conducted with all trainers (N = 4) of the workshops. Results: Day-care teachers evaluated the online training positively, especially the improvement of professionalisation and the implementation of training elements. Results reveal that (work-related) reflexive sessions as well as sessions dealing with the implementation of exercise tools into daily practice were rated as fundamental parts in the training. Teachers from high-risk day-care centres estimated the trainings’ effectiveness lower than those working in low-risk day-care centres. Qualitative data shows that the day-care teachers are in need of (theoretical) knowledge about all training elements and hands-on advice for dealing with specific situations. Especially day-care teachers within a high-risk environment, who already report having an elevated level of intercultural knowledge and skills, may need a higher dose training while low-risk day-care teachers may profit more from a low threshold training. Conclusion: The introduced training sessions focusing on intercultural sensitivity and competence present an important contribution to the professionalisation of day-care teachers in working with children from different cultural backgrounds. Trainings should focus on reflexive elements as well as exercises in perspective taking and provide hands on materials for daily work.